Applicability of WO3-based visible-light photocatalysis for removal of pharmaceuticals and personal care products under real-water conditions - Chee-Hun Han; Seoyeon Park; Jinsoo Cho; Kyung Guen Song; Yongju Choi; Jong Kwon Choe (Journal of Environmental Chemical Engineering, 2026)

Historical and future water quality risks driven by climate change: Strategic management and overcoming challenges - Minhee Kim; Min Jang; Choe Earn Choong; Junho Han (Water Research, 2026)

DNA barcode and sequence related amplified polymorphism markers reveal phylogenetic relationship among Pinus species representing closed lineage divergence - Mi-Ryong Choe; Sam-Rang Song; Un–Hyang Ho; Jong–Gum Ri; Chung-Il Yo; Tong-Ryul Kim; Ok-Hyang Han; Il-Jin Kim; Chol-Ho Kang (Genetic Resources and Crop Evolution, 2025)

Leveraging large language models in pharmacometrics: evaluation of NONMEM output interpretation and simulation capabilities - Hwa Jun Cha; Kyuyeon Choe; Euibeom Shin; Murali Ramanathan; Sungpil Han (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

Yolk-shell nanoparticle-loaded multifunctional membrane with photothermal and advanced oxidation properties - Geun Young Kim; Jeong-Min Park; Hyun-Seok Choe; Han-Gil Kim; Suyoung Jeong; Jae-Hong Kim; Jae-Hyuk Kim (Chemical Engineering Journal, 2025)

Causative mechanisms limiting the removal efficiency of short-chain per- and polyfluoroalkyl substances (PFAS) by activated carbon - Junho Han; Choe Earn Choong; Min Jang; Junghee Lee; Seunghun Hyun; Won-Seok Lee; Minhee Kim (Chemosphere, 2024)

Clinical outcomes and immunological features of COVID-19 patients receiving B-cell depletion therapy during the Omicron era - Chan Mi Lee; Minji Kim; Seong-wook Park; Chang Kyung Kang; Pyoeng Gyun Choe; Nam Joong Kim; Hyeon Jae Jo; Hyun Mu Shin; Chang-Han Lee; Hang-Rae Kim; Wan Beom Park; Myoung-don Oh (Infectious Diseases, 2024)

Analysis of metabolome and transcriptome of longissimus thoracis and subcutaneous adipose tissues reveals the regulatory mechanism of meat quality in MSTN mutant castrated male finishing pigs - Kai Gao; Shengzhong Han; Zhouyan Li; Zhaobo Luo; Sitong Lv; Hak Myong Choe; Hyo Jin Paek; Biaohu Quan; Jindan Kang; Xijun Yin (Meat Science, 2024)

First record of Macaca mulatta (Cercopithecidae: Papionini) from the Taedong River Basin, the Democratic People’s Republic of Korea - Kum Sik Han; Kwang Sik So; Rye Sun Choe; Jun Chol Kang; Il Kang; Chol Ung Ri (Palaeoworld, 2023)

Crotamine-based recombinant immunotoxin targeting HER2 for enhanced cancer cell specificity and cytotoxicity - Jaepyeong Jang; Minh Quan Nguyen; Sangsu Park; Dayoung Ryu; Hyeseon Park; Gunsup Lee; Chong Jai Kim; Yeon Jin Jang; Han Choe (Toxicon, 2023)

Competitive formation of NO, NO2, and O3 in an air-flowing plasma reactor: A central role of the flow rate - Jinwoo Kim; Hyungyu Lee; Seong-Cheol Huh; Jin Hee Bae; Wonho Choe; Duksun Han; Seungil Park; Seungmin Ryu; Sanghoo Park (Chemical Engineering Journal, 2023)

An exact DtN artificial boundary condition for motion analysis of water wave with undulated seabed - Un-Ryong Rim; Gwang-Hyok Choe; Nam-Hyok Ri; Min Hyok Jon; Won-Sik Pae; Un-Hyok Han (Wave Motion, 2023)

Atomic Pt clusters on Au dendrite for formic acid oxidation - Jooyoung Kim; Hyunki Kim; Sungjun Kim; Jue-Hyuk Jang; Hyuntae Sohn; Seok Jin Hong; Junhyeong Kim; Gyeong Ho Han; Seonghyun Choe; Yung-Eun Sung; Soo Young Kim; Ho Won Jang; et al. (Chemical Engineering Journal, 2023)

Association of myostatin deficiency with collagen related disease-umbilical hernia and tippy toe standing in pigs - Hyo-Jin Paek; Zhao-Bo Luo; Hak-Myong Choe; Biao-Hu Quan; Kai Gao; Sheng-Zhong Han; Zhou-Yan Li; Jin-Dan Kang; Xi-Jun Yin (Transgenic Research, 2021)

Hymenobacter taeanensis sp. nov., radiation resistant bacterium isolated from coastal sand dune - Ji Hee Lee; Jong-Hyun Jung; Min-Kyu Kim; Han Na Choe; Sangyong Lim (Antonie van Leeuwenhoek, 2021)

Preliminary investigation of Late Pleistocene fauna from Ryonggok Cave No. 1, Sangwon County, North Hwanghae Province, Democratic People's Republic of Korea - Rye Sun Choe; Kum Sik Han; Se Chan Kim; Myong Hyok Ri; Jae Nam Ri (Journal of Quaternary Science, 2021)
The investigation of a limestone cave on the Ryonggok‐ri of Sangwon County, North Hwanghae Province, DPRK, has yielded many faunal remains including Late Pleistocene deer, brown bears and horses. Uranium series dating of fossil teeth yielded dates of ~72ka at the base of Layer 2 – the bone‐bearing unit – and ~44ka at the top. The rich and diverse mammal remains of Ryonggok Cave No. 1 are indicative of warm and humid temperate conditions during the Late Pleistocene, and reflect the presence of both dense forests and open grassland. In addition, pollen and spores from the site include two families and 24 genera of trees, six families and a genus of grasses and herbs, and two families and six genera of ferns, corroborating the environments inferred from the faunal remains.

Spirosoma taeanense sp. nov., a radiation resistant bacterium isolated from a coastal sand dune - Ji Hee Lee; Jong-Hyun Jung; Min-Kyu Kim; Han Na Choe; Chi Nam Seong; Sangyong Lim (Antonie van Leeuwenhoek, 2021)

Hymenobacter baengnokdamensis sp. nov., Isolated from the Soil of a Crater Lake in Korea - Ji Hee Lee; Min-Kyu Kim; Jong-Hyun Jung; Ho Seong Seo; Jing Zhang; Han Na Choe; Seon Choi; Chi Nam Seong; Sangyong Lim (Current Microbiology, 2020)

The Cardiovascular Effect of Single Injection and Toxicologic Effects of Repetitive 2-Week Intravenous Administration of Activin A/BMP-2 Chimera in Beagle Dog - Jae Hyup Lee; Senyon Choe; Shihuan Han (Cardiovascular Toxicology, 2018)

Piperlongumine induces G2/M phase arrest and apoptosis in cholangiocarcinoma cells through the ROS-JNK-ERK signaling pathway - Sunisa Thongsom; Wipa Suginta; Kyung Jin Lee; Han Choe; Chutima Talabnin (Apoptosis, 2017)

A biology-driven receptor model for daily pollen allergy risk in Korea based on Weibull probability density function - Kyu Rang Kim; Mijin Kim; Ho-Seong Choe; Mae Ja Han; Hye-Rim Lee; Jae-Won Oh; Baek-Jo Kim (International Journal of Biometeorology, 2017)

Mapping Purkinje Cell Placement Along the Purkinje Cell Layer: an Analysis of Postmortem Tissue from Essential Tremor Patients vs. Controls - Elan D. Louis; Daniel Rabinowitz; Matthew Choe; William J. Tate; Geoffrey C. Kelly; Sheng-Han Kuo; Phyllis L. Faust (The Cerebellum, 2016)

New variogram modeling method using MGGP and SVR - Changik Han; Jiyang Wang; Mingguo Zheng; Ende Wang; Jianming Xia; GwangSu Li; Sunchol Choe (Earth Science Informatics, 2016)

Soluble overexpression and purification of bioactive human CCL2 in E. coli by maltose-binding protein - Thu Trang Thi Vu; Bon-Kyung Koo; Jung-A Song; Seon-Ha Chong; Cho Rong Park; Minh Tan Nguyen; Boram Jeong; Han-Bong Ryu; Jae Young Seong; Yeon Jin Jang; Robert Charles Robinson; Han Choe (Molecular Biology Reports, 2015)

VEGF neutralization can prevent and normalize arteriovenous malformations in an animal model for hereditary hemorrhagic telangiectasia 2 - Chul Han; Se-woon Choe; Yong Hwan Kim; Abhinav P. Acharya; Benjamin G. Keselowsky; Brian S. Sorg; Young-Jae Lee; S. Paul Oh (Angiogenesis, 2014)

Class 3 inhibition of hERG K+ channel by caffeic acid phenethyl ester (CAPE) and curcumin - Seong Woo Choi; Kyung Su Kim; Dong Hoon Shin; Hae Young Yoo; Han Choe; Tae Hee Ko; Jae Boum Youm; Woo Kyung Kim; Yin Hua Zhang; Sung Joon Kim (Pflügers Archiv - European Journal of Physiology, 2013)

Constitutive activation of brassinosteroid signaling in the Arabidopsis elongated-D/bak1 mutant - Yuhee Chung; Vitnary Choe; Shozo Fujioka; Suguru Takatsuto; Muho Han; Jong-Seong Jeon; Youn-Il Park; Kyun Oh Lee; Sunghwa Choe (Plant Molecular Biology, 2012)

Polar and Alpine Microbial Collection (PAMC): a culture collection dedicated to polar and alpine microorganisms - Yung Mi Lee; GoHeung Kim; You-Jung Jung; Cheng-Dae Choe; Joung Han Yim; Hong Kum Lee; Soon Gyu Hong (Polar Biology, 2012)

Esculetin promotes type I procollagen expression in human dermal fibroblasts through MAPK and PI3K/Akt pathways - Jung Hae Park; So Ra Kim; Hyun Ju An; Woo Jin Kim; Myeon Choe; Jeong A. Han (Molecular and Cellular Biochemistry, 2012)

Association between OPG, RANK and RANKL gene polymorphisms and susceptibility to acute coronary syndrome in Korean population - WON-SEOK CHOE; HACK-LYOUNG KIM; JUNG-KYU HAN; YOUNG-EUN CHOI; BORAMI SEO; HYUN-JAI CHO; HAN-KWANG YANG; KYU-JOO PARK; JIN-SHIK PARK; HUN-JUN PARK; PUM-JOON KIM; SANG-HONG BAEK; et al. (Journal of Genetics, 2012)

Functional Domain Marker (FDM): an In Silico Demonstration in Solanaceae Using Simple Sequence Repeats (SSRs) - Ju-Kyung Yu; Hyojung Paik; Jae Pil Choi; Jung-Heon Han; Jun-Kyoung Choe; Cheol-Goo Hur (Plant Molecular Biology Reporter, 2010)

Acetylcholine rescues two-cell block through activation of IP3 receptors and Ca2+/calmodulin-dependent kinase II in an ICR mouse strain - Seong-Keun Cho; Sook-Young Yoon; Chang-Gi Hur; Hae-Young Yang; Changyong Choe; Eun-Jin Kim; Jung Soo Joo; Kee Ryeon Kang; Jae-Yong Park; Seong-Geun Hong; Jaehee Han; Dawon Kang (Pflügers Archiv - European Journal of Physiology, 2009)

A Ds-insertion mutant of OSH6 (Oryza sativa Homeobox 6) exhibits outgrowth of vestigial leaf-like structures, bracts, in rice - Sung Han Park; Chul Min Kim; Byoung Il Je; Su Hyun Park; Soon Ju Park; Hai Long Piao; Yuan-hu Xuan; Mi Sook Choe; Kouji Satoh; Shoshi Kikuchi; Kon Ho Lee; Young Soon Cha; et al. (Planta, 2007)

Chemical and physical speciation of mercury in Offatts Bayou: A seasonally anoxic bayou in Galveston Bay - Seunghee Han; Ronald D. Lehman; Key-Young Choe; Gary A. Gill (Limnology and Oceanography, 2007)
A chemical equilibrium model was used to predict the solution speciation of dissolved mercury (Hg) in the stratified water column of Offatts Bayou, a subestuary in Galveston Bay, Texas, which undergoes seasonal anoxia in bottom waters. Chemical equilibrium modeling was conducted using conditional stability constants and concentrations of Hg‐complexing organic ligands experimentally determined by competitive ligand equilibration methods. Dissolved Hg complexation was dominated by interactions with sulfide and dissolved organic matter (DOM) (HOHgHS 0 , HOHgHS(DOM), HgSHS − , and HgS 2 2‐ at all depths. Sulfide and glutathione competed for methylmercury (MeHg) complexation in oxic layers; in anoxic waters, sulfide complexation dominated MeHg speciation. The particle‐water distribution coefficient (K d ) of Hg decreased in the anoxic layer of the water column, where the dissolved sulfide concentration increased, providing evidence that sulfide complexation influences the solubility of Hg. The solubility of MeHg was elevated in the anoxic as compared to the oxic layers, and this distributional feature was coincident with a change in the solution speciation of dissolved MeHg from glutathione/sulfide complexation in the oxic layers to a predominantly sulfide complexation in the anoxic layers. Maximum enrichment of Hg, MeHg, and iron (Fe) in suspended particulate matter was observed in the lower layer of the pycnocline, most likely resulting from formation of insoluble Fe oxide, which scavenged dissolved Hg‐sulfide and MeHg‐sulfide species. The concomitant decrease in dissolved inorganic Hg, Fe, and sulfide in the anoxic layers is suggested to result from scavenging of inorganic Hg by FeS, which is in accordance with the Hg speciation model. Overall, Hg cycling in the water column of Offatts Bayou was associated with sulfide and DOM complexation, Fe dissolution/precipitation, water column production of MeHg, and/or efflux of MeHg from anoxic sediment.

Sediment‐water exchange of total mercury and monomethyl mercury in the San Francisco Bay‐Delta - Key‐Young Choe; Gary A. Gill; Ronald D. Lehman; Seunghee Han; Wesley A. Heim; Kenneth H. Coale (Limnology and Oceanography, 2004)
Five field trips were conducted in the San Francisco Bay‐Delta between May 2000 and October 2001 to investigate the sediment‐water exchange of total mercury (Hg) and monomethyl mercury (MMHg). Solid‐phase Hg averaged ~1 nmol g −1 and did not show any variability with depth or time or among sites. In contrast, solid‐phase MMHg showed considerable vertical, temporal, and spatial variability (0.4–66 pmol g −1 ), with the highest values occurring at a peat‐rich environment in May 2001, suggesting that MMHg production was largely controlled by temporal factors and habitat type. In pore water, both Hg and MMHg concentrations were generally elevated near the sediment‐water interface during warm months. Sediment‐water exchange flux of MMHg, determined with benthic chamber deployments, ranged from −92 to 850 pmol m −2 d −1 , with higher values occurring in May. In most cases, diffusional fluxes of Hg and MMHg, estimated with the use of interfacial concentration gradients, constituted only a minor portion of the measured fluxes, suggesting the importance of advective processes on sediment‐water exchange. Surface‐water transect and time series studies conducted in Franks Tract support the commonly held belief that wetland and marsh regions are major sources for MMHg within the Delta. The integrated sediment‐water fluxes of Hg and MMHg in the study area were estimated to be 130 and 6 mmol d −1 , respectively, and the benthic input was as important a source of Hg and MMHg as the riverine input within the Delta during low‐flow months.

Seasonal Changes of Phytoplankton Communities in the Paksil and Jungyang Marshes - Gyeong-Rak Lee; Jae-Sin Choe; Han-Sun Kim (Algae, 2003)

Growth and Maturation of a Green Alga, Caulerpa okamurae Weber van Bosse - Eun-Gyeong Hwang; Chan-Seon Park; Jeong-U Han; Won-Jun Sin; Chang-Geun Choe; Cheol-Hyeon Son (Algae, 2003)

Native-feather degradation by Fervidobacterium islandicum AW-1, a newly isolated keratinase-producing thermophilic anaerobe - Gae-Won Nam; Dong-Woo Lee; Han-Seoung Lee; Nam-Ju Lee; Byoung-Chan Kim; Eun-Ah Choe; Jae-Kwan Hwang; Maggy Suhartono; Yu-Ryang Pyun (Archives of Microbiology, 2002)

Determination of UDP-N-acetylglucosamine:β-D-mannoside-1,4-N-acetylglucosaminyltransferase-III in patients sera with chronic hepatitis and liver cirrhosis using a monoclonal antibody - Eun-Young Song; Kyung-Sook Kim; Kyoung-A. Kim; Yung-Dai Kim; Dur-Han Kwon; Si-Myung Byun; Hee-Jung Kim; Tae-Wook Chung; Yong-Kyung Choe; Tai -Wha Chung; Cheorl-Ho Kim (Glycoconjugate Journal, 2002)

The timing and characterization of p53 mutations in progression from atypical ductal hyperplasia to invasive lesions in the breast cancer - Joo Kang; Sun Kim; Dong-Young Noh; Kuk Choe; Eun Lee; Han-Sung Kang (Journal of Molecular Medicine, 2001)

Germinal virus vector WDV (wheat dwarf virus)-mediated multiple insertions of a maize transposon,Ds (dissociation), in rice - Hang Gyeong Chin; Sung Han Park; Mi Sook Choe; Su Hyun Park; Byeong Keun Oh; Gi Hwan Lee; Hae Choon Choe; Moo Je Cho; Jong Chan Hong; Chang-deok Han (Journal of Plant Biology, 2000)

A new class II rice chitinase, Rcht2, whose induction by fungal elicitor is abolished by protein phosphatase 1 and 2A inhibitor - Cha Young Kim; Sang Wan Gal; Mi Sook Choe; Sun Yong Jeong; Soo In Lee; Yong Hwa Cheong; Sang Hyoung Lee; Young Ju Choi; Chang-deok Han; Kyu Young Kang; Moo Je Cho (Plant Molecular Biology, 1998)